A indexação da dívida pública à taxa Selic: origem e a persistência após o Plano Real - Chicoski, Davi (2017)
This dissertation analyzes the phenomenon of the Brazilian public debt indexation at the average Selic ("Special System for Settlement and Custody") rate starting from a remarkably post-Keynesian theoretical perspective, in which concepts such as money, interest and public debt are developed. It continues with the historical approach of the global context in which Brazil is inserted and, thereby, it reports how the indexation of financial assets appeared and boosted, which ended with the near-money, the daily indexation at Selic. It stresses that the financial indexation neither implies parting with liquidity nor other considerable risks, especially the market risk. It discusses the financial indexation of the public debt at high interest, while a mechanism interfering in investment and production, because it confers prestige to short-term financial investments and carry trade operations. It analyzes this indexation impacts on the public debt trajectory, the monetary policy and the income distribution. It points out that the discussion does not consist in technical and neutral aspects, but reveals a political conflict over the national income, in which the financial indexation mechanisms privilege financial and rentiers sectors